Strain Engineering of Ferroelectric Domains in KxNa1−xNbO3 Epitaxial Layers - Schwarzkopf, Jutta; Braun, Dorothee; Hanke, Michael; Uecker, Reinhard; Schmidbauer, Martin (Frontiers in Materials, 2017)
The application of lattice strain through epitaxial growth of oxide films on lattice mismatched perovskite-like substrates strongly influences the structural properties of ferroelectric domains and their corresponding piezoelectric behavior. The formation of different ferroelectric phases can be understood by a strain-phase diagram, which is calculated within the framework of the Landau-Ginzburg-Devonshire theory. In this paper, we illustrate the opportunity of ferroelectric domain engineering in the KxNa1-xNbO3 lead-free material system. In particular, the following examples are discussed in detail: (i) Different substrates (NdGaO3, SrTiO3, DyScO3, TbScO3, GdScO3) are used to systematically tune the incorporated epitaxial strain from compressive to tensile. This can be exploited to adjust the NaNbO3 thin film surface orientation, and, concomitantly, the vector of electrical polarization, which rotates from mainly vertical to exclusive in-plane orientation. (ii) In ferroelectric NaNbO3 thin films grown on rare-earth scandate substrates, highly regular stripe domain patterns are observed. By using different film thicknesses, these can be tailored with regard to domain periodicity and vertical polarization component. (iii) A featured potassium concentration of x = 0.9 of KxNa1 xNbO3 thin films grown on (110) NdScO3 substrates favors the coexistence of two equivalent, monoclinic, but differently oriented ferroelectric phases. A complicated herringbone domain pattern is experimentally observed which consists of alternating MC and a1a2 domains. The coexistence of different types of ferroelectric domains leads to polarization discontinuities at the domain walls, potentially enabling high piezoelectric responses. In each of these examples, the experimental results are in excellent agreement with predictions based on the linear elasticity theory.